Сost-effectiveness of the second wave of protease inhibitors in the treatment of chronic hepatitis C (genotype 1) in patients not previously treated with antiviral drugs, and for relapsed disease - A. V. Rudakova; D. A. Gusev; A. N. Uskov; L. N. Konovalova; Yu. V. Lobzin (Журнал инфектологии, 2016)
The protease inhibitors (PI) actively using for the treatment of chronic hepatitis C (CHC).The aim of this analysis was to evaluate the cost-effectiveness of narlaprevir and simeprevir in the CHC (genotype 1) therapy in treatment-naïve patients and relapses.Material and methods. Analysis of the cost-effectiveness of simeprevir and narlaprevir was conducted from the perspective of the health care system and base on QUEST-1, QUEST-2, ASPIRE and PIONEER clinical trials. The relative risk of achieving SVR 24 compared to the peg-INF + RBV therapy was used in the model. Treatment discontinuation in patients receiving narlaprevir assumed in the absence of a SVR after 12 weeks and in patients receiving simeprevir in the SVR absence after 4 weeks. The cost of narlaprevir was calculate based on estimated registration price in case of EDL (essential pharmaceutical list approved by MOH) inclusion, including VAT (10%) and 10% as trade margin. Costs of other antiviral products were in line with the results of 2015 average auctions prices.Results. In the base case costs on antiviral products with narlaprevir as first-line therapy are lower compared with simeprevir by 12,2% (950,6 and 1083,0 thousand RUR, respectively), and the cost per patient with SVR 24 by 7,8%. In patients group after relapse costs on antiviral products with narlaprevir as first-line therapy will decrease compared with simeprevir by 4,3% (971,3 and 1014,7 thousand RUR, respectively), and the cost per patient with SVR 24 by 25,0%. The sensitivity analysis demonstrated a high reliability of obtained results. Thus, assuming equal clinical effectiveness of narlaprevir and simeprevir, costs of treatment naive patients will be 10.6% lower for narlaprevir group compared to simeprevir group (953,0 and 1066,0 thousand rur, respectively), and by 12,9% for the treatment of relapses (957,9 and 1100,0 thousand RUR, respectively).Conclusions. With comparable clinical efficacy and tolerability of narlaprevir and simeprevir both in treatmentnaïve patients and patients with relapse after therapy, which included PEGylated interferon and ribavirin, narlaprevir reduces the burden on the budget. Due to substantial variability of PI prices, it is advisable to take into account local pricing at regional programs implementation.